2023
DOI: 10.3389/fpls.2023.1200071
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolomics-based analysis of sugar composition and content in berries of 18 grape varieties

Abstract: Xinjiang is the largest grape-producing region in China and the main grape cultivation area in the world. The Eurasian grape resources grown in Xinjiang are very rich in diversity. The sugar composition and content are the main factors that determine the quality of berries. However, there are currently no systematic reports on the types and contents of sugars in grapes grown in Xinjiang region. In this research, we evaluated the appearance and fruit maturity indicators of 18 grape varieties during fruit ripeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…This was consistent with a previous report that the total sugar of Pondoh Super was higher (14.50%) than Pondoh Madu (13.38%) and Pondoh Gading (12.37) [23]. Sugar content in fruit is influenced by variety and maturity level [22]. It was reported that the sugar content increased during ripening, and the reducing sugar content was related to the gritty texture of the salak Pondoh [11].On the other hand, the total soluble solids of the six varieties ranged from 22.55 to 23.83 Brix.…”
Section: A Chemical Characteristic Of Salak Fruitsupporting
confidence: 93%
See 1 more Smart Citation
“…This was consistent with a previous report that the total sugar of Pondoh Super was higher (14.50%) than Pondoh Madu (13.38%) and Pondoh Gading (12.37) [23]. Sugar content in fruit is influenced by variety and maturity level [22]. It was reported that the sugar content increased during ripening, and the reducing sugar content was related to the gritty texture of the salak Pondoh [11].On the other hand, the total soluble solids of the six varieties ranged from 22.55 to 23.83 Brix.…”
Section: A Chemical Characteristic Of Salak Fruitsupporting
confidence: 93%
“…The pH value of Sari Intan was reported to be related to total acid concentration. Salak with a higher pH has less total acid [22]. Sari Intan 48 had lower total acid (0.82) than Sari Intan 295 (0.51-1.23) and 541(0.34-1.25).…”
Section: A Chemical Characteristic Of Salak Fruitmentioning
confidence: 88%
“…Kliewer found a broader variation among 26 Vitis species from North America and the Middle East, with TSS at maturity spanning from 13.7 Brix in V. champinii to 31.5 Brix in V. riparia from Wyoming (Kliewer 1967b ). Furthermore, among 18 Eurasian grape species in Xinjiang region, the TSS at maturity have been reported to vary widely, from as low as14.9 Brix in Victoria to as high as 25.1 Brix in Summer Black (Zhong et al 2023 ). In terms of specific sugar types, all cultivars primarily accumulate glucose and fructose, typically glucose content ranging from 42.13 to 46.80% of the total sugar and the fructose contents varied from 42.68 to 50.95%, while exhibiting very low levels of sucrose which varied from 6.17 to 12.69% (Zhong et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, among 18 Eurasian grape species in Xinjiang region, the TSS at maturity have been reported to vary widely, from as low as14.9 Brix in Victoria to as high as 25.1 Brix in Summer Black (Zhong et al 2023 ). In terms of specific sugar types, all cultivars primarily accumulate glucose and fructose, typically glucose content ranging from 42.13 to 46.80% of the total sugar and the fructose contents varied from 42.68 to 50.95%, while exhibiting very low levels of sucrose which varied from 6.17 to 12.69% (Zhong et al 2023 ). Conversely, V. labrusca and V. rotundifolia , along with their interspecific hybrids, are noted for higher sucrose levels, ranging from 5 to 58.28 g/L, along with moderate concentrations of glucose and fructose (from 35 to 54 g/L), marking a distinct contrast in sugar profiles (Dai et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Dylan et al., 2022 ). Currently there are fewer reports on whether nanomaterials can regulate the growth and development of grapevines ( Zhong et al., 2023 ). Our laboratory has developed a new nano fertilizer.…”
Section: Introductionmentioning
confidence: 99%